Skills and Functioning Departmentalization in Improving The Effectiveness of Digitalization of Accounting Systems - Lilis Puspitawati; Nadya Shaffira; Pearl Fafa Bansah (Australasian Accounting, Business and Finance Journal, 2024)
Business sustainability is an essential issue in the age of globalization, and it reinforces the value of quality information in the strategic decision-making process. Management accounting information systems are alleged to have a strategic role in producing quality accounting information, which is ultimately influenced by managerial considerations and the level of workforce expertise. This study seeks to identify the substances that influence the efficacy of management accounting information systems. Quantitative analysis was performed to find out the association between the variables tested. Questionnaires have been sent to 132 managerial accountants from Indonesian state-owned businesses. The method of selection used consisted of simple random sampling, and the resultant sample size for this study was 72 participants. The data were analyzed using Structural Equation Modeling (SEM) on Lisrel software version 8.5. The investigation's findings reveal that skill and departmentalization are substantially related to the effectiveness of management accounting information systems. Nevertheless, this needs to be reinforced by business strategy elements. The present investigation revealed that the competencies and tasks performed by departmentalized business units play a substantial part in the effectiveness of establishing a management accounting information system in Indonesian state-owned firms.
Keywords: Digital Business Model; Strategic Information; User Ability; Departmentalization; Business Sustainability